2010
DOI: 10.1124/jpet.109.162479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exposure Route and Oral Dosage Regimen on 1, 1-Dichloroethylene Toxicokinetics and Target Organ Toxicity

Abstract: The objective of this investigation was to elucidate the effects of route of exposure and oral dosage regimen on the toxicokinetics (TK) of 1,1-dichloroethylene (DCE). Fasted male Sprague-Dawley rats that inhaled 100 or 300 ppm for 2 h absorbed total systemic doses of (10 or 30 mg/kg DCE, respectively. Other groups of rats received 10 or 30 mg/kg DCE by intravenous injection, bolus gavage (by mouth), or gastric infusion (g.i.) over a 2-h period. Serial microblood samples were taken from the cannulated, unanest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For urinary elimination of total radioactivity, the estimated half-lives for the first and second phases were 6 and 17 hours for both doses. Plasma toxicokinetics of vinylidene chloride in Sprague Dawley rats following gavage exposure showed a similar behavior to inhalation exposure 18 . The Cmax and AUC0-∞ following gavage exposure to 30 mg/kg were 8.9 mg/L and 233 μg•min/mL, respectively; the elimination half-life and bioavailability were 88 minutes and 46.5%, respectively.…”
Section: Absorption Distribution Metabolism and Excretion Experimementioning
confidence: 69%
See 1 more Smart Citation
“…For urinary elimination of total radioactivity, the estimated half-lives for the first and second phases were 6 and 17 hours for both doses. Plasma toxicokinetics of vinylidene chloride in Sprague Dawley rats following gavage exposure showed a similar behavior to inhalation exposure 18 . The Cmax and AUC0-∞ following gavage exposure to 30 mg/kg were 8.9 mg/L and 233 μg•min/mL, respectively; the elimination half-life and bioavailability were 88 minutes and 46.5%, respectively.…”
Section: Absorption Distribution Metabolism and Excretion Experimementioning
confidence: 69%
“…An investigation of the plasma toxicokinetics of vinylidene chloride in Sprague Dawley rats showed that the Cmax and AUC0-∞, respectively, following inhalation exposure to 300 ppm were 2.8 mg/L and 279 μg•min/mL; the elimination half-life and bioavailability, respectively, were 50 minutes and 55.7% 18 .…”
Section: Absorption Distribution Metabolism and Excretion Experimementioning
confidence: 99%
“…The research area was located near the chemical industry park. The groundwater had been polluted due to unreasonable discharge of wastewater containing benzene (BZ) and dichloroethylene (DCE), both of which are organic pollutants with the highest detection rate in the groundwater of this research area and both of which pose a threat to human health 22,23 . This study chose BZ and DCE as typical pollutant indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The groundwater had been polluted due to unreasonable discharge of wastewater containing benzene (BZ) and dichloroethylene (DCE), both of which are organic pollutants with the highest detection rate in the groundwater of this research area and both of which pose a threat to human health. 22,23 This study chose BZ and DCE as typical pollutant indicators. By analyzing the 13 C isotopes of BZ and DCE and the fractionation of 13 C and 14 C isotopes in the total dissolved inorganic carbon (DIC), the natural attenuation capacity of organic pollutants in the groundwater of the study area was evaluated and the microbial degradation processes were quantitatively described.…”
Section: Introductionmentioning
confidence: 99%